PENGARUH PEMBELAJARAN QUANTUM TEACHING BERBANTU POWERPOINT TERHADAP HASIL BELAJAR SISWA PADA MATERI CAHAYA KELAS VIII SEMESTER II SMP SWASTA HKBP SIDORAME MEDAN T.P. 2013/2014 - Desy Christina N. Panjaitan; Derlina Nasution (UNIVERSITAS NEGERI MEDAN, 2015)
The purpose of this research is to find out the effect of student’s outcomes by using Quantum Teaching assisted powerpoint. The average value of student outcomes treated by using Quantum Teaching assisted powerpoint is 68.27 and the conventional learning is 57.25. The learning activities of students during the learning by using Quantum Teaching assisted powerpoint including active criteria with the percentage 64.13% . Based of the calculation of t test analysis, which tcount>ttable = (3,866 > 1,67), so that there is a significant difference to the student’s outcomes by using Quantum Teaching assisted learning powerpoint . Key Words: Quantum Teaching learning, activities, learning outcomes.